Registration of Mining Business Permits in the Indonesian Minerba One Data System (MODI) of the Ministry of Energy and Mineral Resources Reviewed from the Perspective of State Administrative Law - Muh. Rustiawan Ardiansyah; Ahmad Redi (Indonesian Journal Publisher, 2026)
This study examines the Mining Business Permit (IUP) registration regulations in the Minerba One Data Indonesia (MODI) system of the Ministry of Mineral Resources and Energy from the standpoint of State Administrative Law. The study problem's primary focus is on how the Minister of Energy and Mineral Resources' Decree Numbers 15.K/HK.02/MEM.B/2022 and 297.K/MB.01/MEM.B/2023 differ in their IUP registration regulations and how this affects how State Administrative Court rulings are implemented. The normative legal research method used in this study includes a statutory regulatory approach, a comparison approach, and a case approach. Both primary legal resources, like laws and court decisions, and secondary legal resources, such as relevant books and academic publications, are used. The findings demonstrate that legally binding court rulings are still accepted by the Minister of Energy and Mineral Resources' Decree Number 15 of 2022 as the foundation for processing and registering IUPs in the MODI system. However, this approach was modified by the Minister of Energy and Mineral Resources Decree No. 297 of 2023, which concentrated on the organization and reconciliation of licensing data by the national and local governments. This difference in regulation has the potential to create a conflict between administrative policies and the obligation to implement court decisions, as reflected in the PT Gapura Mario Sejahtera dispute. The Supreme Court's decision in this case emphasized that administrative policies cannot override the obligation of state administrative officials to implement legally binding court decisions.